The basics of digital forensics : the primer for getting started in digital forensics - Sammons, John (Basics., 2015)
This book provides a foundation for those new to the digital forensics field and teaches how to conduct examinations by discussing what digital forensics is, the methodologies used, key tactical concepts, and the tools needed to perform examinations. Details on digital forensics for computers, networks, cell phones, GPS, the cloud and the Internet are discussed. The second edition features expanded resources and references, including online resources, sample legal documents, and suggested further reading. You will learn what digital forensics entails; learn how to collect evidence, document the scene, and how deleted data can be recovered; build a toolkit and prepare an investigative plan; understand the common artifacts to look for in an exam. There is new coverage of hard drives, triage, network intrusion response, and electronic discovery; as well as updated case studies, and expert interviews. --